La naturaleza jurídica de la retención a cuenta. Una aproximación desde la imposición sobre la renta - Mares Ruíz, Carla (Revista de Derecho, 2019)
Tax withholding is a juridical institute -which we could regard as “classical”- present in existing tax figures in most juridical ordainments. It was constituted as a feature of some product taxes and, later with the evolution of fiscal systems, of personal taxes. In a first instance, it became clear that what was legal was not the retention: it was not set as an independent tribute; neither was it identified with the tax with operated it. Retention was presented as an inserted mechanism, out of the law’s will, in the light of a wider tributary obligation. Nonetheless, it was necessary to establish its juridical nature, above all, due to the implications that the application of this mechanism brings about within the dynamics of a tax and which affect, mostly, those who intervene in the retention. The posture adopted regarding the nature of the retention determines the configuration of the subjects who intervene in it. This issue has had as a result several study pages. Pages which we try to systematize and analyze in the present article.
Keywords: Tax withholding; anticipated payment; retainer; autonomous obligation; provision on account